The Effect of Relationship Marketing and Customer Satisfaction on Customer Loyalty at PT. Bank Muamalat Indonesia - Verawaty, Verawaty; Talawa, Musdalifa (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
This study aims to find out and analyze the influence of relationship marketing and customer satisfaction on customer loyalty at PT. Bank Muamalat Indonesia Tbk Makassar Branch. The type of research used is quantitative. The population in this study is customers at PT. Bank Muamalat Indonesia Tbk Makassar Branch. Sample selection uses the purposive sampling method. The data collection method uses a questionnaire. The statistical method used in this study is the multiple linear regression method and uses SPSS 22.0 software. The results of the study show that relationship marketing has a positive and insignificant effect on customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty. Simultaneously, relationship marketing and customer satisfaction have a significant effect on customer loyalty.